2022
DOI: 10.1111/jcmm.17505
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming barriers in bovine cells nuclear transfer revealed by single‐cell RNA‐seq analysis

Abstract: Many progresses have recently been achieved in animal somatic cell nuclear transfer (SCNT). However, embryos derived from SCNT rarely result in live births. Single‐cell RNA sequencing (scRNA‐seq) can be used to investigate the development details of SCNT embryos. Here, bovine fibroblasts and three factors bovine iPSCs (3F biPSCs) were used as donors for bovine nuclear transfer, and the single blastomere transcriptome was analysed by scRNA‐seq. Compared to in vitro fertilization (IVF) embryos, SCNT embryos exhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 63 publications
(120 reference statements)
0
11
0
Order By: Relevance
“…After use of stringent quality-control filters to ensure the construction of a high-quality database, we obtained 14 single-cell DNA and RNA libraries. We reanalyzed the single-cell RNA-seq data extracted from the PRJNA727165 public data set [33] of bovine in vitro fertilization embryo samples for uniform manifold approximation and projection (UMAP) analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After use of stringent quality-control filters to ensure the construction of a high-quality database, we obtained 14 single-cell DNA and RNA libraries. We reanalyzed the single-cell RNA-seq data extracted from the PRJNA727165 public data set [33] of bovine in vitro fertilization embryo samples for uniform manifold approximation and projection (UMAP) analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Consistent with previous studies [23,24], pluripotency-related genes and oocyte-marker genes were highly expressed in both blastocyst-developed and arrested embryos, while granulosa cell marker genes were not expressed (Figure 1E). We combined our eight-cell embryo data with all stages of preimplantation embryos from a recent study [33] and performed an integrated single-cell RNA analysis. The global expression pattern of all samples further confirmed that blastomeres from eight-cell embryos were collected correctly (Supplementary Figure S1D).…”
Section: Single-cell Multi-omics Sequencing To Determine the Developm...mentioning
confidence: 99%
“…We collected single-cell sequencing data from published literature for comparative analysis. Two Bovine IVF single-cell sequencing raw FASTQ data were downloaded from the GEO database, including 179 IVF cells 35 sequenced using Smart-seq2 and 98 IVF cells 36 sequenced using STRT-seq.…”
Section: Published Single-cell Data Collectionmentioning
confidence: 99%
“…Data availability 8 cell and 16 cell from GSE99210 (Single-cell RNA sequencing reveals developmental heterogeneity of blastomeres during major genome activation in bovine embryos) 28 . Zygote, 2 cell, 8 cell, morula and blastocyst from PRJNA727165 (Reprogramming barriers in bovine cells nuclear transfer revealed by single cell RNA seq analysis) 27 . Raw unprocessed data of gastrulation embryos was obtained from Dr. Peter L. Pfeffer 29 .…”
Section: Pseudotime Constructionmentioning
confidence: 99%
See 1 more Smart Citation